On the Efficiency of Forced Air Cooling of Frictional Connections of Brake Devices - Volchenko, N.A.; Balonniy, V.T.; Skrypnyk, V.S.; Nasirova, M.M.; Ostashuk, N.M.; Zhuravlev, D.Y.; Vitvitskiy, V.S. (Herald of Azerbaijan Engineering Academy, 2021)
The materials of the article are devoted to the features of forced, direct cooling with moist compressed air of the working surfaces of friction pairs of brake devices. The results of a computational experiment concerning the design parameters of the cooling system and its operational parameters are presented. The efficiency of air cooling of the drum-shoe brake friction pairs is estimated. Attention is paid to the peculiarities of forced cooling with moist compressed air of brake tribo couplings. Compressed air pressures have been established, at which it is possible to forcibly cool the friction pairs of drum-shoe and band-shoe braking devices.